All edible materials derived biocompatible and biodegradable triboelectric nanogenerator. (November 2019) - Khandelwal, Gaurav; Minocha, Tarun; Yadav, Sanjeev Kumar; Chandrasekhar, Arunkumar; Maria Joseph Raj, Nirmal Prashanth; Gupta, Subash Chandra; Kim, Sang-Jae
Abstract: The energy crisis and plastic pollution are of growing concern worldwide. Nanogenerators converting mechanical energy to electrical energy would be of assistance. Triboelectric nanogenerators (TENGs) are inexpensive, simple to fabricate, and afford high output, as revealed by extensive research over the past decade. However, most TENGs use a polymer as either the substrate or the active layer, contributing to plastic pollution. Biodegradable/edible devices are required; they are harmless when discarded. We here derive a single-electrode lightweight TENG (E-TENG) using only edible materials. Laver coated with an edible silver leaf serves as the active layer and a rice sheet as the substrate. We analyzed surface potential, morphology, and roughness; laver was triboelectrically active. The results of the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay, cell imaging, and 4′, 6-diamidino-2-phenylindole (DAPI) staining suggest that the device minimally affected cell viability. The device was bioresorbable in phosphate-buffered saline (PBS) and gastric acid. Output performance was tested using paper, tissue paper, polyvinyl chloride (PVC), and fluorinated ethylene propylene (FEP). The electrical performance was systematically studied; an FEP-laver E-TENG performed best (output of 23 V and current of 315 nA). The output was used to power a hygrometer, a wristwatch, green light-emitting diodes (LEDs), and ultraviolet (UV) LEDs. Graphical abstract: Edible triboelectric nanogenerator is demonstrated. The Laver is frictional layer with edible silver leaf as electrode in single electrode E-TENG. The MTT assay, Live-dead imaging and DAPI staining suggest minimal effect. The device provides an output of 23 V and 315 nA. The large device is used to drive wristwatch, hygrometer and LEDs.Image 1 Highlights: A single-electrode, lightweight all edible material based triboelectric nanogenerator (ETENG) was fabricated using Laver. The cell studies and bioresorbable experiments confirm the biocompatibility and biodegradability of the device. Using an FEP layer, E-TENG generated 23 V and 315 nA. The device was used to drive a wristwatch, a hygrometer, and LEDs.